RESEARCH ON ACOUSTIC RADIATION CHARACTERISTIC OF SAW BLADE CUTTING SYSTEM BASED ON MULTI-FIELD COUPLING - TIAN YongJun; DUAN GuoLin; YAO Tao; GANG JianHua; ZHANG E (Jixie qiangdu)
In order to study the distribution of sound field and quantitative estimates of the cutting noise,a multiphysics coupling model was constructed.Firstly,the vibration response of the fluid structure interaction system was extracted under multibody dynamic contact by using method of center difference.Moreover,a co-simulation method for the acoustic radiation model based on the boundary element method and acoustic coupling theory was presented.On this basis,a structure acoustic coupling model was established to calculate the sound pressure according to the results of the vibration response previously calculated.Then,the sound radiation in time domain characteristics and domain characteristics with the coupled system in half the space is studied.On the basis of the FSI theory,the computing results of the one-way coupling method and two-way coupling method are compared.Finally,the effects of radiating area influence on the sound power is discussed,makes clear the primarily radiation area.As compared with the experimentation results,the multi-field coupling model established in this paper about cutting noise of the saw blade is correct and feasible.